Problem Formulation and Resolution in Online Problem-Based Learning - Kenny, Richard F.; Bullen, Mark; Loftus, Jay (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
This paper discusses an exploratory study to investigate the existence, and nature, of student problem formulation and resolution processes in an undergraduate online Problem-Based Learning (PBL) course in Agricultural Sciences. We report on the use of a content analysis instrument developed to measure problem formulation and resolution (PFR) processes in online asynchronous discussions (Murphy, 2004a, 2004b) to analyze students' text-based, online discussions. The results offer evidence that students do engage in problem formulation and resolution and that these processes appear to be consistent with the PBL process carried out in this course. However, the nature of the PBL pedagogy, at least in this instructional context, ties the PBL problems to be solved tightly to a marked assignment structure and, therefore, appears to restrict the PFR process in its early and late stages.